Distinct polymer-dependent sorption of persistent pollutants associated with Atlantic salmon farming to microplastics. (July 2022) - Abihssira-García, Isabel S.; Kögel, Tanja; Gomiero, Alessio; Kristensen, Torstein; Krogstad, Morten; Olsvik, Pål A.
Abstract: Interactions of microplastics and persistent organic pollutants (POPs) associated with Atlantic salmon farming were studied to assess the potential role of microplastics in relation to the environmental impact of aquaculture. HDPE, PP, PET and PVC microplastics placed for 3 months near fish farms sorbed POPs from aquafeeds. PET and PVC sorbed significantly higher levels of dioxins and PCBs compared to HDPE, while the levels sorbed to PP were intermediate and did not differ statistically from PET, PVC or HDPE. In addition, the composition of dioxins accumulated in caged blue mussels did not reflect the patterns observed on the microplastics, probably due to polymer-specific affinity of POPs. In conclusion, the results of this study show that microplastics occurring near fish farms can sorb aquafeed-associated POPs and, therefore, microplastics could potentially be vectors of such chemicals in the marine environment and increase the environmental impact of fish farming. Graphical abstract: Unlabelled Image Highlights: Microplastics bind pollutants associated to fish feed used in Atlantic salmon farming. PET and PVC sorb more amount of dioxins and PCBs compared to HDPE. Mussels do not reflect the POPs composition sorbed to microplastics.